New Meanings, Old Words. (Writing)
This article presents information on new meanings and old words. The Internet has forever changed the way we speak and write. For starters, it has introduced new vocabulary into the English dictionary-words such as Cyberspace, e-mail, etiquette and, of course, google, a trademark which is commonly used as a noun and a verb. The Net has also expanded the meanings we attribute to existing words and expressions words such as spam, cookie, bookmark, surfing, and mouse. Avatar in the Hindu religion is a representation of God in superhuman or animal form now it is an icon or image that represents the Cyberspace "you." Java is an Island in Indonesia; brewed coffee now it is a programming language that is used to create interactive Web pages.